Improved strontium segregation suppression of lanthanum strontium cobalt oxide cathode via chemical etching and atomic layer deposition - Kim, Dong hwan; Yang, Sungeun; Kwon, Deok Hwang; Ji, Ho Il; Son, Ji-Won; Shim, Joon Hyung (John Wiley & Sons Inc., 2022)
This study was conducted to improve the stability of a high-performance cathode, which plays a crucial role in lowering the operating temperature of solid oxide fuel cells (SOFCs) to below 600 degrees C while retaining its performance. Lanthanum strontium cobalt oxide (LSC) is a representative SOFC cathode material used in the intermediate temperature (IT) region (500 degrees C-600 degrees C). When segregation occurs on the cathode surface during high-temperature fabrication, the initial performance degrades to a certain extent, followed by continuous performance degradation. Herein, we aimed to overcome this degradation through surface modification. Accordingly, an ideal LSC surface composition was achieved by removing the segregated Sr through wet chemical etching of the cathode surface. Further, an atomic layer deposition (ALD) process of less than 1 nm thickness was introduced to prevent further Sr separation and minimize performance degradation. The peak power density of the cell with the modified surface (M-LSC) at 550 degrees C was 509 mW cm(-2), whereas that of the cell with bare LSC was 483 mW cm(-2). Based on the 70-h short-term stability test, the bare LSC showed a degradation of 70 mV, while the M-LSC remained stable with no degradation.